2023
DOI: 10.5194/isprs-annals-x-4-w1-2022-677-2023
|View full text |Cite
|
Sign up to set email alerts
|

Flood Susceptibility Modelling Using Geospatial-Based Multi-Criteria Decision Making in Large Scale Areas

Abstract: Abstract. Flood is one of the most hazardous natural disasters that cause damages and poses a major threat to human lives and infrastructures worldwide, and its prevention is almost unfeasible. Thus, the detection of flood susceptible areas can be a key to lessen the amount of destruction and mortality. This study aims to implement a framework to identify flood potential zones in an ungauged large-scale area with frequent flood events in recent years. We used two Multi-Criteria Decision Making (MCDM) approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The situation is aggravated by the lack of knowledge and contingency plans on the part of the population and local authorities. Likewise, several authors [56][57][58] have found that densely populated areas are the most affected by floods, while less populated and higher areas present are less at risk. Both studies mention that the direct relationship between population density, the quality of housing infrastructure, drainage infrastructure and vulnerability to flooding contributes to the generation of risks as observed in the results presented, which also emphasize that urban flooding can cause property damage, loss of life and the spread of waterborne diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The situation is aggravated by the lack of knowledge and contingency plans on the part of the population and local authorities. Likewise, several authors [56][57][58] have found that densely populated areas are the most affected by floods, while less populated and higher areas present are less at risk. Both studies mention that the direct relationship between population density, the quality of housing infrastructure, drainage infrastructure and vulnerability to flooding contributes to the generation of risks as observed in the results presented, which also emphasize that urban flooding can cause property damage, loss of life and the spread of waterborne diseases.…”
Section: Discussionmentioning
confidence: 99%